Analisis Pertanggungjawaban Pidana terhadap Pelaku Tindak Pidana Pembunuhan Pengidap Skizofrenia Paranoid - Putri Cahya Andrianti; Firganefi Firganefi; Sri Riski; Eko Raharjo (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2025)
Criminal liability, also known as "criminal responsibility," is a legal assessment that is made after all elements of a criminal act are met or evidence of a criminal act is proven. The purpose of this assessment is to determine whether the defendant can be held accountable for the criminal act committed. This study specifically focuses on criminal liability for the perpetrator of murder who is a person with paranoid schizophrenia, as well as the factors that influence the act of murder. The approaches used in this study are normative juridical and empirical juridical juridical The research involved the Judge of the Gedong Tataan District Court and a Psychiatrist at the Regional Psychiatric Hospital of the University of Lampung as the main speakers. Data collection was carried out through literature studies and field studies to obtain a comprehensive picture related to the legal, medical, psychological, and social aspects of the case being studied. The results of the study show that the defendant, even though it is legally proven that he committed a criminal act as stated in Decision No. 105/Pid.B/2023/PN.Gdt, is bound by the provisions of Article 5 letter a juncto Article 44 Paragraph (3) of Law Number 23 of 2004 concerning the elimination of domestic violence. However, based on judicial, medical, and psychological considerations, the defendant cannot be criminally held liable for his actions for excused reasons related to mental disorders. Factors that affect this act of murder include psychological aspects, psychological conditions, mental health, traumatic experiences, and the social and family environment in which the perpetrator grew up. The analysis shows the importance of an integrative understanding between criminal law, psychiatry, and social conditions in determining criminal liability.